The Role of Media and Communication in Reducing Uncertainty During the Syria War - Kozman, Claudia (2021)
Ten years after the uprising in Syria, millions of its citizens remain displaced and uncertain about their fate. Throughout that period, media coverage about the ensuing civil war played a major role in informing Syrians and contributed to altering their levels of fear and anxiety about their country’s future and their survival prospects. This study examined the role of legacy media, online media, and interpersonal communication in increasing or reducing uncertainty among displaced and non-displaced Syrians. Through a revised construct of uncertainty reduction theory within the context of a civil war, we assessed the relationship between exposure to these media sources and feeling anxious, uncertain, angry, and in danger, and whether these feelings influenced information consumption trends. We also probed the connection between their anxiety levels and sharing information, both interpersonally and on social media. The study surveyed 2,192 Syrian adults (95% CI, ±2.5) living in Syria, Lebanon, Jordan, and Turkey, both inside and outside refugee camps, using a random multistage cluster sampling technique. The findings revealed a strong relationship between positive emotions and time spent on legacy and online media. The more secure, proud, and hopeful people felt, the more likely they were to spend time on media sources. This relationship, however, was moderated by the perceived importance of these sources. Feelings of pride, security, and hopefulness generated by television and online media correlated with the time people spent on these media sources, and the perceived importance of such media further strengthened this relationship. A different picture appeared in the relationship between positive emotions and interpersonal communication, where the perceived importance of talking to people not only significantly moderated the relationship but also canceled out the main effect of positive emotions on the time people spend communicating with others. The findings also indicated that feelings of uncertainty about these sources may stand in the way of sharing information about the war on social media.